Social-Emotional Learning Interventions for Students With Special Educational Needs: A Systematic Literature Review - Hassani, Sepideh; Schwab, Susanne (Frontiers in Education, 2021)
In the last decades, social-emotional learning interventions have been implemented in schools with the aim of fostering students’ non-academic competences. Evaluations of these interventions are essential to assess their potential effects. However, effects may vary depending on students’ variables. Therefore, the current systematic review had three main objectives: a) to identify the effectiveness of social-emotional learning interventions with students with special educational needs, b) to assess and evaluate those intervention conditions leading to effective outcomes in social-emotional competences for this population, and c) to draw specific conclusions for the population of students with special educational needs. For this purpose, studies were retrieved from the databases Scopus, ERIC, EBSCO and JSTOR, past meta-analysis and (systematic) reviews, as well as from journal hand searches including the years 1994 to 2020. By applying different inclusion criteria, such as implementation site, students’ age and study design, a total of eleven studies were eligible for the current systematic review. The primary findings indicate that most of the intervention studies were conducted in the United States and confirm some positive, but primarily small, effects for social-emotional learning interventions for students with special educational needs. Suggestions for future research and practice are made to contribute to the improvement of upcoming intervention studies.